To Triumph or to Socialize? The Role of Gaming Motivations in Multiplayer Online Battle Arena Gameplay Preferences. (April 2022) - Bonny, Justin W.; Castaneda, Lisa M.
Background: Individuals choose to engage in multiple types of online team-based video games. Gameplay options allow for player preferences to shape their gaming experience. Within the multiplayer online battle arena (MOBA) genre, players can decide whether to play matches with familiar or random teammates and whether their performance impacts their skill rating. Individual differences in video game engagement and genre preferences have been connected with player motivations and uses of video games and psychological traits that influence social interactions. The present study examined the extent to which the match preferences of MOBA players related to these factors. Methods: Individuals attending an international MOBA tournament were recruited for the present research. Player MOBA match selection history was collected along with questionnaires measuring video game uses and gratifications, preference for solitude, tolerance of disagreement, and a test of theory of mind ability. Results: Three main findings were observed. First, the highest-rated video game motivation was to socially interact with others. Second, players that displayed different preferences for types of MOBA matches varied in social interaction and competition video gameplay motivation scales. Third, although individual differences in fantasy video game motivation were correlated with theory of mind ability and preference for solitude, they did not vary by MOBA match preferences. Conclusion: The results of the present study indicated that MOBA players were more strongly motivated by social aspects of video gameplay and variations in video game motivation to compete correlated with the extent to which they engaged in different types of MOBA play.